PENGARUH HARGA, KUALITAS LAYANAN JARINGAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PRIME NEW INDOSAT (Studi Kasus Pengguna Kartu Indosat di Galeri Kantor Pusat PT Indosat Ooredoo Hutchison) - Arga Pradana; Supartono Supartono; Kurbandi Satpatmantya BR (Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of price, network service quality, and promotion on purchasing decisions of Indosat's flagship new product (a case study on Indosat card users at PT Indosat Ooredoo Hutchison's head office gallery), either partially or simultaneously. The data used in this research is primary data. The population in this study are Indosat card users who use the Prime New service at the Gallery Head Office of PT Indosat Hutchison. The total population is 4,800. The sample used in this study amounted to 369 respondents, with the sample selection method using purposive sampling method. The results of this study indicate that the variables of price, network service quality, and promotion have an effect on purchasing decisions